Early Phase Process Evaluation: Industrial Practices - Zulfan Adi Putra (Universitas Pendidikan Indonesia, 2016)
Process route evaluation is a part of research and development (RD) works in an industrial chemical project life cycle. In this early phase, good process evaluation, including process synthesis and designs, provide guidance’s on the RD project. The paper aimed to collect practical methods used in this early phase process route evaluation from author’s 10 years of industrial experiences. The collected methods range from forward-backward process synthesis, functional process design, use of cost estimation, and applications of Monte Carlo simulation. Led by a good project management (e.g. via a stage-gate approach) use of these methods have shown beneficial results. Some important results are strong arguments on whether or not the project will continue, as well as relevant technical and economic issues identified during this early phase process synthesis and design. Later on, these issues become guidance’s to the follow-up project, if it is continued.